2011
DOI: 10.1007/s12247-011-9110-x
|View full text |Cite
|
Sign up to set email alerts
|

De-risking Scale-up of a High Shear Wet Granulation Process Using Latent Variable Modeling and Near-Infrared Spectroscopy

Abstract: In the development of wet granulated drug products, two primary sources of variance (disturbance) include the operational scale of the high shear wet granulation (HSWG) process and active pharmaceutical ingredient (API) lot-to-lot variability, particularly for formulations containing a high drug load. This paper presents a novel Process Analytical Technology strategy using latent variable modeling with nearinfrared spectroscopy (NIRS) to reduce risk in scale-up operations of the HSWG process while simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Besides, two distance criteria, i.e., Hotelling's T 2 and Q residual, 21) were utilized to assess the validity of the LW-PLSR model for a query. Kamohara et al 22) and Muteki et al 23) reported that T 2 and Q could test the validity of the PLSR model for the query. In the previous research, 13) we demonstrated that the assessment based on T 2 and Q was also valuable for testing whether the LW-PLSR model was valid for the query.…”
Section: Calibration Datasetmentioning
confidence: 99%
“…Besides, two distance criteria, i.e., Hotelling's T 2 and Q residual, 21) were utilized to assess the validity of the LW-PLSR model for a query. Kamohara et al 22) and Muteki et al 23) reported that T 2 and Q could test the validity of the PLSR model for the query. In the previous research, 13) we demonstrated that the assessment based on T 2 and Q was also valuable for testing whether the LW-PLSR model was valid for the query.…”
Section: Calibration Datasetmentioning
confidence: 99%
“…Eberle et al (117) showed that through iterative application of PLS and ANOVA analysis, the most frequent causes of yield loss could be identified and improved. To prevent drug product quality from being affected by undesired variability of incoming raw materials, Muteki et al (118) showed that the effects of raw materials could be modeled using a latent-variable approach. A subsequent optimization can then eliminate such variabilities by strategically combining raw materials in later processing steps.…”
Section: Incorporating a Variety Of Data In Randdmentioning
confidence: 99%
“…Applications of LVRM inversion have been proposed in the pharmaceutical industry for raw material acceptance, 15 process development and optimization, 19,28 and process scale-up. 29,30 Although all the above-mentioned studies used LVRM inversion to solve different kinds of problems, the objective function being minimized has often been tailored to the specific case study. In this paper we present a general framework to perform LVRM inversion, which includes several possible different cases which one may encounter in a product/process design exercise.…”
Section: Introductionmentioning
confidence: 99%